A novel cytokinin transporter is involved in local root signalling, modulating lateral root emergence - Tessi, Tomás María (2018)
Aerial and underground organs of plants response to the environment modulating their architecture via tightly coordinated processes. Most of these processes are regulated by the morphogenic hormones auxins and cytokinins (CKs). Recently, hormone transport is being considered as a major modulator in hormone signa- lling. However, contrary to auxins, little is known about CK transport. In this work the Arabidopsis transporter AtAZG2 is studied. Although it was first described as a purine transporter, AtAZG2 is also able to take up CKs. Molecular evolution analysis revealed the presence of an AZG homolog in Charophytes (K. flaccidum) - the first known organism with complete CKs signalling pathway. Interestingly, molecular diversification of this transporter family occured in Tracheophytes, the first plants with complex roots. This is interesting regarding AtAZG2 expression domain, which is restricted to few cells surrounding the lateral root (LR) primordia. Furt- hermore, AtAZG2 KOs show lower LR density than Wt suggesting that AtAZG2 is part of a LR emergence re- gulatory pathway. To locally study the relevance of AtAZG2, the CK reporter TCSn:GFP was analysed in KOs. Quantification revealed weaker activity of the reporter in KOs compare to Wt, suggesting a direct link between AtAZG2 CK transport and LR emergence.